O espírito e a carne: a crítica de Bergson e Merleau-Ponty à ontologia objetivista - Temporal, Vanessa de Oliveira (Universidade Federal de São Carlos, 2019)
The basic aim of this thesis is to investigate the concepts of image in Henri Bergson (1859-1941) and of form in Maurice Merleau-Ponty (1908-1961). Bearing in mind the trajectory that these concepts play on both authors’ works, regarding the plenitude of existence into philosophy, as well as the way by which they are characterized as a counterpoint to the artificiality of abstract symbols, we question ourselves the philosophical potential to approach them. Taking into account their motor and vital natures, could there be a similarity in the way they structure philosophical enquiry? We are going to demonstrate that these concepts come close to each other insofar as they integrate a common project, namely the project of undertaking a phenomenal field and replacing the subject of the transcendental field for life itself as a condition for knowledge.

Dans le cadre de cette thèse, nous souhaitons investiguer les concepts d’image chez Henri Bergson (1859-1941) et de forme chez Maurice Merleau-Ponty (1908-1961). En tenant compte le parcours que ces concepts jouent dans leurs oeuvres, en ce qui concerne apporter la plénitude de l’existence vers l’intérieur de la philosophie, ainsi que la façon dont ils sont caractérisés en contraste avec l’artificialité des symboles abstraits, nous nous demandons s’il y aurait la possibilité d’un rapprochement entre les deux. Considérant leurs natures motrice et vitale, est-ce qu’il y aurait une similarité dans la voie qu’ils ouvrent vers la recherche philosophique? Nous essayons de démontrer que ces concepts se rapprochent d’autant qu’ils intègrent un projet commun aux deux philosophes, à savoir, celui d’entreprendre un champ phénoménal capable de remplacer le sujet reflexif du champ transcendantal par la vie elle-même en tant que condition de possibilité de la connaissance.
The spirit and the flesh: Bergson and Merleau-Ponty's criticism on objectivist ontology
L'esprit et la chair: critique de Bergson et Merleau-Ponty à l'ontologie objectiviste
Keywords: Henri Bergson; Maurice Merleau-Ponty; Ontologia; Ontologie; Ontology; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA